A quantum dot-based fluorescence sensing platform for the efficient and sensitive monitoring of collagen self-assembly. (24th June 2020) - Zhong, Huaying; Zhu, Weizhe; Yan, Zihan; Xu, Chengzhi; Wei, Benmei; Wang, Haibo
Abstract : An efficient and sensitive assay for monitoring collagen self-assembly is presented. Abstract : Self-assembly is one of the most vital molecular behaviors of natural collagen, which plays a prominent role in the design and fabrication of collagen-based biomaterials. However, an efficient and sensitive assay for monitoring collagen self-assembly is still lacking. Herein, we developed a quantum dot (QD)-based fluorescence sensing platform and applied it to monitor collagen self-assembly. Before collagen self-assembly, we observed a strong fluorescent signal when ZnCdSe/ZnS QDs were introduced to grass carp skin collagen (GCSC). After self-assembly, the formation of collagen fibril networks induced the aggregation of QDs, resulting in the fluorescence quenching of QDs and a significant decrease in the intensity of fluorescence. Moreover, the quenching efficiency was found to be linearly dependent with GCSC concentration in the range of 0.1–1 mg mL −1, with a detection limit of 0.1 mg mL −1 . In addition, the proposed strategy displayed excellent specificity and wide applicability. These results provide guidance for the design of collagen-based biomaterials and help to deeply understand the mechanism behind collagen self-assembly.